Multiple myeloma: A literature review - Accioly, Mariana Abreu; Bezerra, Heline de Mendonça; Barreto, Livia Solidade; Castro, Melina Fernandes; da Silva , Hélio Bezerra (Seven Editora, 2024)
Multiple myeloma (MM) is a malignant neoplasm characterized by clonal proliferation of plasma cells in the bone marrow and production of monoclonal immunoglobulin, the changes caused by the disease are related to progressive bone destruction, kidney failure, suppression of hematopoietic and higher risk of infections. It is the second most common hematological neoplasm, being slightly more frequent in men. DOI:https://doi.org/10.56238/sevened2024.015-016